Quasi-three dimensional hydraulic design and performance calculation of high specific speed mixed-flow pump. Issue 1 (May 2016) - Su, M; Zhang, Y X; Zhang, J Y; Hou, H C
Abstract: According to the basic parameters of 211-80 high specific speed mixed-flow pump, based on the quasi-three dimensional flow theory, the hydraulic design of impeller and its matching spaced guide vanes for high specific speed mixed flow pump was completed, in which the iterative calculation of S 1, S 2 stream surfaces was employed to obtain meridional flow fields and the point-by-point integration method was employed to draw blade camber lines. Blades are thickened as well as blade leading edges are smoothed in the conformal mapping surface. Subsequently the internal fields of the whole flow passage of the designed pump were simulated by using RANS equations with RNG k-ε two-equation turbulent model. The results show that, compared with the 211-80 model, the hydraulic efficiency of the designed pump at the optimal flow rate increases 9.1%. The hydraulic efficiency of designed pump in low flow rate condition (78% designed flow rate) increases 6.46%. The hydraulic efficiency in high flow rate areas increases obviously and there is no bad phenomenon of suddenly decrease of hydraulic efficiency in model pump. From the distributions of velocity and pressure fields, it can be seen that the flow in impeller is uniform and the increase of pressure is gentle. There are no obvious impact phenomenon on impeller inlet and obvious wake shedding vortex phenomenon from impeller outlet to guide vanes inlet.